Potentials of walnut (tetracarpidium conophorum Mull. Arg) leaf and onions (allium cepa linn) bulb extracts as antimicrobial agents for fish (2013)
The zone of inhibition varied with the bacteria and type of extract. The average diameter of inhibition zones was 10 ± 0.00 and 9 ± 0.02 mm for methanolic and ethanolic extracts of walnut leaves and onion bulbs, respectively. Staphylococcus aureus, B. subtilis and P. aeruginosa were most sensitive to the extracts. However, S. aureus was more sensitive to the extracts of walnut leaves and S. typhi was the least sensitive. Bacillus subtilis was more sensitive to the extracts of onion compared to E. coli which was the least sensitive. Minimum inhibitory concentration of walnut leaves and onion bulbs extracts on the bacteria tested were both 500 ìg/ml. The results indicated that walnut leaves and onion bulbs had antibacterial activity on the tested organisms and showed their prospects for their use in the treatment of fish diseases